The house of Dies Drear and related readings - Hamilton, Virginia, 1936-2002. (New York : Glence/McGraw-Hill, 2000)
An African American family tries to unravel the secrets of their new home in Ohio which was once an important station on the Underground Railroad.
Sequel: The mystery of Drear House.
Keywords: African Americans -- Juvenile fiction; African Americans -- Fiction; Mystery and detective stories; Underground Railroad -- Fiction; Ohio -- History -- 20th century -- Fiction